2013
DOI: 10.1186/2049-2618-1-29
|View full text |Cite
|
Sign up to set email alerts
|

Daily temporal dynamics of vaginal microbiota before, during and after episodes of bacterial vaginosis

Abstract: BackgroundBacterial vaginosis (BV) is a common gynecologic diagnosis characterized by dysbiosis of the vaginal microbiota. It is often accompanied by vaginal symptoms such as odor and discharge, but can be asymptomatic. Despite over 50 years of research, the etiology of BV is not well understood, which is a major impediment to treatment and prevention of BV.ResultsHere we report on the temporal dynamics of 25 vaginal communities over a 10 week period using samples collected daily from women who were diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
330
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 270 publications
(341 citation statements)
references
References 26 publications
8
330
1
2
Order By: Relevance
“…Notably, few or no reads of Lactobacilli species were found in the samples from arboreal monkeys (howlers, lemurs and red colobus). Reads classified to the genus Gardnerella appeared to be undersampled from human samples (and possibly from NHP samples too) in this study, compared with previously published reports (Kim et al, 2009;Ravel et al, 2013). This may be attributed to not including the primer cocktail (27F-YM þ 3), as described in Frank et al, 2008. Recent studies (Zhou et al, 2010;Ravel et al, 2011;Ravel et al, 2013) have revealed Lactobacillus spp.…”
Section: Resultsmentioning
confidence: 46%
See 3 more Smart Citations
“…Notably, few or no reads of Lactobacilli species were found in the samples from arboreal monkeys (howlers, lemurs and red colobus). Reads classified to the genus Gardnerella appeared to be undersampled from human samples (and possibly from NHP samples too) in this study, compared with previously published reports (Kim et al, 2009;Ravel et al, 2013). This may be attributed to not including the primer cocktail (27F-YM þ 3), as described in Frank et al, 2008. Recent studies (Zhou et al, 2010;Ravel et al, 2011;Ravel et al, 2013) have revealed Lactobacillus spp.…”
Section: Resultsmentioning
confidence: 46%
“…Reads classified to the genus Gardnerella appeared to be undersampled from human samples (and possibly from NHP samples too) in this study, compared with previously published reports (Kim et al, 2009;Ravel et al, 2013). This may be attributed to not including the primer cocktail (27F-YM þ 3), as described in Frank et al, 2008. Recent studies (Zhou et al, 2010;Ravel et al, 2011;Ravel et al, 2013) have revealed Lactobacillus spp. in low abundance in the vaginal tract of a subpopulation of apparently healthy women with high Nugent scores, who have been categorized as 'asymptomatic BV' (ABV) in contrast to 'symptomatic BV' (SBV) subjects.…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…To this end, we took advantage of a preexisting clinical study focused on understanding the dynamics of the vaginal microbiome. In this study, vaginal samples were collected daily from 135 nonpregnant women over the course of 10 wk (Ravel et al 2013). To test if the PDGF BB and NEDD9 pathways are activated during clinical episodes of vaginal candidiasis, we performed RNA-seq using RNA isolated from vaginal swabs that were collected as part of this study.…”
Section: Transcriptomic Evidence For Activation Of Pdgf Bb and Erbb2 mentioning
confidence: 99%